Anatomical and functional outcomes of surgery of rhegmatogenous retinal detachment - Thakur, SKD (Nepalese Journal of Ophthalmology, 2011)
DOI: 10.3126/nepjoph.v3i1.4295 Nepal J Ophthalmol 2011;3(5):93